Adie's syndrome as a cause of amblyopia (1987)
Adie's syndrome comprises a tonic pupil, which may be associated with impairment of accommodation, in the presence of diminished or absent deep tendon reflexes. We report a case of a 4-year-old boy with Adie's syndrome in which latent hypermetropia was made manifest by accommodative paresis and resulted in reversible amblyopia